Optimum capacity of the inverters in concentrator photovoltaic power plants with emphasis on shading impact. (15th November 2019) - Rodrigo, P.M.; Talavera, D.L.; Fernández, E.F.; Almonacid, F.M.; Pérez-Higueras, P.J.
Abstract: Nowadays, there is wide experience on selecting an adequate ratio between the photovoltaic array peak power and the inverter capacity for conventional photovoltaic systems. However, when dealing with concentrator photovoltaic plants, the problem is more complex and the results obtained with conventional methods are not directly applicable. There are few studies regarding concentrator photovoltaic technology and all of them neglect the impact of shading. In this paper, based on the experimental characterisation of a typical concentrator photovoltaic module, a power plant model is developed, which takes into consideration shading, module misalignment, and different inverter configuration schemes for optimising the inverter capacity. The inverter size is analysed for different ground cover ratios (from 12% to 52%), inverter schemes (micro-, string-, and tracker-inverters), inverter efficiencies (low-, medium-, and high-efficiency), climatic conditions (Granada, Marrakech, and Frenchman Flat), and economic conditions (system cost excluding inverters from 850 to 1400 €/kWp). Results show values for the DC-to-AC sizing ratio ranging from 1.01 to 1.67 (maximum performance ratio), and from 1.53 to 1.79 (minimum levelised cost of energy). String-inverters exhibit the best behaviour in terms of levelised cost of energy, except in shadow-free systems, in which tracker-inverters behave better. Highlights: The inverter capacity in concentrator photovoltaics is analysed considering shading. Maximum performance ratio and minimum levelised cost of energy are searched. Shading cannot be neglected when maximising the performance ratio. The economic optimum DC-to-AC sizing ratio is higher than the energetic optimum. String-inverters are the best option in terms of levelised cost of energy.